The Impact of Marital Instability and Psychological Distress on Quality of Life among Married Women, Pakistan - Batool, Aqsa; Bajwa, Ruqia Safdar; Farooq, Sidra; Ayub , Muhammad (Pakistan Journal of Humanities and Social Sciences, 2023)
The impact of marital instability and psychological distress on quality of life extends beyond the emotional realm. They can also affect other domains, such as physical health, social relationships, and overall life satisfaction. The motive of the study was to examine the effect of marital instability and psychological distress on quality of life among early and late married women in Pakistan. A cross-sectional research design was adopted. A purposive sampling design using a cross-sectional design was employed. A sample of 200 women, containing 100 early married women and 100 late married women, was taken from different divisions of Southern Punjab, Pakistan. A survey consisting of three key questionnaires, namely the Kessler Psychological Distress Scale (K10), the WHO-Quality of Life Scale (BREF), and the Marital Instability Index (MII), was used for data collection. The findings evinced that marital instability has a positive and significant relationship with psychological distress among women with early and late marriages. Moreover, a higher level of marital instability and psychological distress with a low quality of life was found among early or late married women. Comparatively, women with early marriages have a higher level of marital instability and psychological distress and a lower level of quality of life as compared to women with late marriages. Overall, the study's findings recommended proactive interventions and policies aimed at improving the psychological well-being and quality of life of women in the region.